Long-Term Efficacy of Neoadjuvant Concurrent Chemoradiotherapy for Potentially Resectable Advanced Siewert Type II and III Adenocarcinomas of the Esophagogastric Junction - Tian, Yuan; Wang, Jun; Qiao, Xueying; Zhang, Jun; Li, Yong; Fan, Liqiao; Zhang, Zhidong; Zhao, Xuefeng; Tan, Bibo; Wang, Dong; Yang, Peigang; Zhao, Qun (Frontiers in Oncology, 2021)
Background: Reports have shown that neoadjuvant concurrent chemoradiotherapy (nCRT) increases the R0 resection rate for patients with Siewert type II or III adenocarcinoma of the gastroesophageal junction (AEG). However, the long-term efficacy of nCRT for AEG patients remains unclear. In this multicenter study, we investigated the long-term results of AEG patients treated with nCRT. Methods: A total of 149 patients with potentially resectable advanced AEG (T3/4, Nany, M0) were randomly divided into 2 groups: the nCRT-treated group (treated group) (n=76) and the surgery group (control group) (n=73). The primary endpoint was disease-free survival (DFS), and the secondary outcome indexes included the R0 resection rate, HER-2 expression, tumor regression grade (TRG), objective response rate (ORR), disease control rate (DCR), overall survival (OS) and adverse events. Results: In the treated group, the overall therapeutic efficacy rate was 40.8%, and the pathological complete response (pCR) rate was 16.9%. The rates of patients who underwent R0 resection in the treated and control groups were 97.0% and 87.7%, respectively (P<0.05). The toxic effects were mainly graded 1–2 in the treated group. The median DFS times in the treated and control groups were 33 and 27 months, respectively (P=0.08), whereas the median OS times were 39 and 30 months, respectively (P=0.02). The median DFS times of patients with positive and negative HER-2 expression in the treated group were 13.5 and 43 months, respectively (P=0.01), and the median OS times were 26.5 and 41 months, respectively (P=0.01). Conclusion: Surgery after nCRT improved the efficacy of treatment for AEG patients and thus provided a better prognosis. The trial is registered with ClinicalTrials.gov (number NCT01962246).